NEGATIVE EFFECTS OF THE EXPECTED MARMARA EARTHQUAKE - ÖZBAY, Onur (SSD Journal, 2024)
The anticipated Marmara Earthquake is not only expected to be one of the most significant natural disasters Turkey will face but also poses severe threats to national security. The impacts of the earthquake will extend beyond physical destruction, triggering profound social, economic, political, and security-related consequences. Factors such as infrastructure damages, economic instability, lack of social resilience, security threats, inadequacies in healthcare services, and misinformation will further complicate the national security dimensions of the Marmara Earthquake. This article provides a comprehensive analysis of the potential security threats and their implications for Turkey's national interests in the aftermath of the earthquake. Firstly, the discussion addresses how infrastructure destruction will disrupt public order and daily life. Then, the economic instability resulting from the earthquake, including its effects on unemployment rates, inflation, and businesses, will be explored. Within the context of social resilience, the analysis focuses on how the insufficiency of societal support mechanisms post-disaster could lead to social unrest. Furthermore, security threats will be examined in terms of potential social upheavals and situations jeopardizing public safety in the aftermath of the disaster. Healthcare inadequacies and misinformation are evaluated as critical factors that could exacerbate post-disaster chaos. Lastly, the article presents recommendations for managing these challenges, emphasizing how local administrations and the central government can better prepare for the anticipated disaster.